Espiritualidade e sobrecarga de cuidadoras idosas com e sem dificuldade para dormir - Iroldi, Grazielle Ferreira (Universidade Federal de São Carlos, 2023)
Spirituality and overload of women older caregivers with and without difficulty sleeping In the Brazilian context, the responsibility for caring for the older people is commonly attributed to female family members. Daily care tasks can lead to complaints related to difficulty sleeping, generate overload, affect physical and mental health, as well as reduce the time the caregiver spends on work, spiritual and leisure activities. This research aims to verify whether there is an association between self-reported difficulty sleeping, overload and spirituality of women older caregivers of elderly people. This is a descriptive, quantitative and cross-sectional study that will compare data from older women who are informal caregivers of older people treated at Family Health Units in the city of São Carlos - SP, divided into two groups: (a) Group of womem older caregivers without self-reported sleeping difficulties (b) Group of womem older caregivers with self-reported sleeping difficulties. The data collection instruments used were: (a) Characterization Form for Womem Older Caregivers, (b) Spirituality Assessment Scale by Pinto and Pais-Ribeiro and (c) Zarit Burden Scale – Short Version. The data obtained were entered into a bank using the Statistical Package for Social Sciences (SPSS) for Windows program to carry out descriptive and comparative statistical analyses. The sample had a mean age of 68.92 years (Md=67.00; xmín=60,00; xmáx=98,00),), 3.67 years of schooling (Md=4.00; xmín=0,00; xmáx=18,00), individual and family income of 0 .89 and 3.10 minimum wages (individual and family, respectively). Most were married or had a partner (91.3%, n=240), white (68.1%, n=179), Catholic (63.9%, n=168), practicing a religion (81 .4%, n=214), retired (61.2%, n=161), with insufficient income perception (52.2%, n=138) and without health insurance (79.5%, n=209). With regard to the characteristics of care, the responsibility of caring for the spouse was the most frequent (n=230, 87.5%) followed by parents (n=17, 6.5%) and siblings (n=12, 4, 6%). The care, for the most part, was performed without training (n=255, 97.0%), for long periods of time (M=122.37 months, Md=60.0, xMín=0,00; xMáx=708,00) and long hours daily (M=6.00, Md=4.00, xMín=1,00; xMáx=24,00). The prevalence of self-reported difficulty sleeping was 51.7%. Comparative analyzes revealed significant differences between groups, caregivers with difficulty sleeping presenting the highest total burden score (U=7328.00; p=0.034) and caregivers without difficulty sleeping presenting the highest total spirituality score (U=7270.50; p=0.020). It is concluded that womem older caregivers with sleeping difficulties have a greater burden and less spirituality when compared to caregivers without sleeping difficulties.
Spirituality and overload of women older caregivers with and without difficulty sleeping
Keywords: Idoso; Cuidadores; Sono; Estresse psicológico; Espiritualidade; Elderly; Caregivers; Sleep; Psychological stress; Spirituality; CIENCIAS DA SAUDE::SAUDE COLETIVA